A COMPARATIVE STUDY OF THREE TACTILE MAP PRINTING TECHNIQUES IN THE DESIGN OF EDUCATIONAL MATERIALS FOR VISUALLY IMPAIRED STUDENTS - Nhan Minh, Truong; The Trung, Le; Duc Hieu, Ta; Thi Nga, Hoang (HNUE Journal of Science: Journal of Educational Science, 2025)
Maps are important teaching tools that help develop spatial thinking in students; for visually impaired students, tactile maps play an especially significant role. Currently, three common techniques are used to produce tactile maps: Thermoform, Swell, and 3D printing. This study compares the suitability of these techniques in the design of educational materials for visually impaired students in Ho Chi Minh City. Using questionnaire surveys combined with in-depth interviews, the research findings show that all 14 experts encountered no difficulties in using the Thermoform technique, which effectively meets both the needs and practical conditions of schools. This study also emphasizes the crucial role of teaching aids, especially tactile maps, in developing the qualities and competencies of visually impaired students within the context of inclusive education in mainstream schools.